Union of the Comoros : 2010 Article IV Consultation and Second Review Under the Extended Credit Facility, Request for Modification of a Performance Criterion, and Financing Assurances Review-Staff Report; Staff Statement and Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Comoros. (IMF Staff Country Reports; Country Report, 2011)
The policies in a challenging political and economic environment are discussed in this study. The importance of reforms to enhance the budget process, tax administration, and expenditure control is encouraged. A higher growth path will require far-reaching structural reforms to bolster Comoros's competitiveness and increase the economy's ability to intermediate remittances and aid inflows. The need to improve the business environment and the management of public utilities is explained in detail.